(untitled) (American Innovator: Journal of Emerging Technologies and Research, 2026)
This article examines the pedagogical conditions, methodological approaches, and didactic mechanisms for developing the academic and intellectual abilities of students enrolled in primary education programs. The relevance of the topic is determined by the growing need to prepare future primary school teachers who are capable of independent thinking, analytical reasoning, creative problem-solving, and effective professional decision-making in modern educational environments. The study considers academic and intellectual abilities as an integrated system that includes cognitive activity, logical thinking, reflective skills, information processing, learning motivation, and the ability to apply knowledge in new pedagogical situations. Special attention is given to the role of student-centered instruction, problem-based learning, interactive methods, researchoriented tasks, and reflective practice in strengthening intellectual growth. The article argues that the development of these abilities requires not only the transmission of subject knowledge, but also the purposeful organization of educational processes that stimulate comparison, analysis, synthesis, evaluation, and pedagogical interpretation. It is emphasized that higher pedagogical education should create conditions in which students become active participants in learning, capable of setting academic goals, selecting appropriate strategies, and evaluating their own progress. The proposed ideas may contribute to improving the professional training of future primary education specialists and increasing the quality of pedagogical preparation in higher education